The development of group cohesion as it relates to satisfaction with adult Sunday school - Page, William Lloyd (Kansas State University, 2009)
Educators across the religious spectrum claim that the quest for spirituality and issues related to spiritual fulfillment are important to Americans. Nevertheless, only twenty percent of evangelical churches are growing. The rest are either not growing or are declining in attendance numbers (White, 2003). Many in the field of church growth have come to the conclusion that churches that are growing and meeting the needs of people are those that create within their membership a sense of belonging to a group which is achieved primarily through their Sunday School programs. The purpose of this qualitative case study is to explore the effect, if any, that developing close personal relationships in an adult Sunday School class has on increasing a person’s desire to attend. The work of Francis (2005), Mims (2001), Taylor (2003), and others indicates this is the case and that there are three basic facets of this development. The first is purposefully organizing adult Sunday School classes as age-graded cohorts. The second is designing lessons that involve student interaction through the use of group projects and group discussion, as is the case with lessons that follow the Experiential Learning Model. The third is to provide social opportunities for class members outside of class time. Data was gathered through semistructured interviews administered to members of a young adult Sunday School class which was created expressly for this study. The interview protocol was designed to allow the participants as much freedom as possible to express their own views. Six major themes emerged from the data: 1) young adults value being a part of a stable group; 2) age-grading Sunday School classes enhances relationship building; 3) young adults appreciate the support they get from the class; 4) extracurricular activities help build relationships; 5) relationships are more important to women than to men; and 6) the Experiential Learning Model facilitates relationship building. These results could help shape the way in which evangelical churches approach their Sunday School program design and development in order to facilitate ministering to people more effectively.
Keywords: Sunday school; Adult education; Cohort education; Education, Adult and Continuing (0516)